Analysis of multifunctional sma/piezoelectric/composite beam structure for morphing and energy harvesting - Mallik N. (My University, 2025)
This paper deals with morphing and energy harvesting analysis of new innovative multifunctional hybrid composite beam structure consisting of conventional fiber reinforced composite as substrate layer, a shape memory alloy fiber reinforced composite layer for the purpose of morphing actuation and a piezoelectric composite layer for the purpose of energy harvesting. One dimensional Tanaka type model using Reuss scheme with multi variant martensite is adopted to model SMA behavior and transformation model of SMA solved numerically as Young’s modulus depends on martensite fraction. Multicell micromechanics approach is adopted to calculate effective properties of fiber reinforced composites. The objective of the present work is to analytically investigate the free and forced vibration of this newly proposed hybrid composite beams in pre/post-buckled domains and also to analytically estimate energy harvesting capability. © 2019 9th ECCOMAS Thematic Conference on Smart Structures and Materials, SMART 2019. All rights reserved.